Answer:
- plain cheese $11.45
- each topping $1.30
Step-by-step explanation:
Let c represent the price of a cheese pizza (no toppings), and t represent the price of a topping.
c + 3t = 15.35 . . . . cost of a 3-topping pizza
c + 5t = 17.95 . . . . cost of a 5-topping pizza
__
Subtract the first equation from the second.
(c +5t) -(c +3t) = (17.95) -(15.35)
2t = 2.60 . . . simplify [equation 3]
t = 1.30 . . . . . divide by 2
Then the cost of the cheese pizza is ...
c = 15.35 -3t = 15.35 -3(1.30) = 11.45
A plain cheese pizza costs $11.45; each topping costs $1.30.
_____
<em>Comment on the working</em>
If you're paying attention to what the problem statement is telling you, you should be able to arrive at "equation 3" without much thought. The 5-topping pizza differs from the 3-topping pizza only in the price of 2 toppings. Once you know the price of a topping, figuring the base price of the pizza is not hard.